Analysis of the incidence and influencing factors of frailty in maintenance hemodialysis patients - Wang Yun; Zhu Ling-bo; Liu Jun-jun; Luo Yan-ping (Linchuang shenzangbing zazhi)
Objective To explore the current status of debilitating patients on maintenance hemodialysis and analyze their psychosocial factors.Methods A convenient sampling method was adopted for 180 patients on maintenance hemodialysis from February 2017 to February 2019.Medical records and laboratory tests were reviewed for collecting general and clinical data.Deterioration Scale, Pittsburgh Sleep Quality Index, Hospital Anxiety & Depression Scale, Psychological Resilience Scale, Chronic Disease Self-Efficacy Scale and Perceived Social Support Scale were employed for evaluating patient debilitating condition, sleep quality, anxiety & depression, psychological resilience, self-efficacy and social support.Logistic regression analysis was performed for variables with statistical differences in univariate analysis.Results A total of 176 valid questionnaires were recovered and 11/176 patients（6.3%）suffered from debilitation.Logistic regression analysis indicated that the influencing factors were age, comorbidities, depression, sleep disorders, psychological resilience and social support（P<0.05）.Conclusions Age, comorbidities, depression and sleep disorders are risk factors for frailty and psychological resilience and social support is a protective factor for frailty.Nursing staff should evaluate patient frailty and health status early, adopt targeted nursing strategies, delay the progression of comorbidities, improve sleep quality, control depression symptoms, promote mental health and promote social support.